Negative-k and positive-k layers introduced into graphene/polyvinylidene fluoride composites to achieve high-k and low loss - Zongxiang Wang; Kai Sun; Yunpeng Qu; Zhongyang Wang; Jiahong Tian; Xiaofeng Li; Runhua Fan (Materials & Design, 2021)
Polymer matrix composites (PMCs) with high-k and low loss (tanδ) have aroused extensive research due to their significant applications in energy-storage capacitors and novel printed circuit board. In this work, the single layer structured graphene/polyvinylidene fluoride (GR/PVDF) composites were synthesized by hot pressing process, in which the fascinating permittivity transition from positive to negative was attributed to plasma oscillation. Meanwhile, the alternating current conductivity (σac) and reactance behavior were well consistent with Jonscher’s power law and equivalent circuit model. More importantly, the GR/PVDF composites consisted of negative-k layer that led to high-k and low tanδ performances. When the GR content of the negative-k layer was 10 wt% and positive-k layer was 2 wt%, the permittivity reached up to 559 and tanδ was just 0.053 at 100 kHz in bilayer structured composite, respectively. Theoretically, the high-k performance originated from strong interfacial polarization between positive-k and negative-k layers, which is beneficial to the synergistic effect of capacitive and inductive characters. Additionally, the low tanδ was attributed to the effectiveness restriction of electron transfer in capacitive layer. Therefore, the multilayer structured GR/PVDF composites by introducing negative-k layer can achieve high-k and low loss that supply a novel strategy for preparing dielectric materials.